Produção e caracterização de Ricota Caprina adicionada de bactérias Probióticas - Meira, Quênia Gramile Silva (2015)
Products such as cheeses, yoghurts and milk drinks can be obtained from goat's milk are an alternative to the increase in consumption and value of goatderived products. This study aimed to produce ricotta cheese from goat whey and evaluate the effects of incorporating probiotic strains Bifidobacterium lactis BB-12 and Lactobacillus acidophilus LA-5 on technological parameters, physicochemical and sensory cheese during storage refrigerated for seven days, and the protective effect of goat ricotta on the survival of probiotics tested for exposure to simulated gastrointestinal conditions. A Ricotta goat was prepared based on goat cheese whey (main ingredient) with addition of whole goat milk (20%). The incorporation of probiotics did not influence the income and syneresis of goat ricotta. During the rated cold storage period, the strains L. acidophilus LA-5, and B. lactis BB-12 had scores of about 6 log CFU / g. Samples ricotta containing the probiotic strains showed the lowest values for lactose and the highest values for lactic acid, besides having greater hardness and lower brightness during storage when compared to samples without probiotics. There were no differences in the fatty acid profile of goat ricotta with or without probiotics. All samples of ricotta were sensorially described as "soft cheese" with "homogeneous texture", however, the samples added L. acidophilus LA-5 or B. lactis BB-12 were described as "more acidic". At the end of exposure to simulated gastrointestinal conditions, the tested probiotic strains showed scores of approximately 6 log CFU / g, when incorporated in goat ricotta. These results show the possibility of using L. acidophilus LA-5, and B. lactis BB-12 in the preparation of goat ricotta, considering that such strains showed no negative impact on the general quality characteristics of the product. Further, goats show the ricotta as a satisfactory matrix for the continued viability of probiotics tested during storage as well as when exposed to the harsh conditions found throughout the human gastrointestinal tract.